Efficacy of alprostadil in patients with diabetic nephropathy with different types of Irisin gene rs16835198 - 孙玥; 崔丽娟; 蒿自睿; 赖玉林 (Linchuang shenzangbing zazhi)
Objective To analyze the efficacy of alprostadil in patients with diabetic nephropathy（DN）with different types of the Irisin gene rs16835198.Methods A total of 110 patients with DN treated in our hospital from June 2018 to October 2019 were used as the research object;and all patients were treated with alprostadil.Polymorphism of the Irisin gene rs16835198 in the patients was detected.The blood total cholesterol（TC）,triacylglycerol（TG）,low density lipoprotein cholesterol（LDL-C）,high density lipoprotein cholesterol（HDL-C）,homocysteine（Hcy）,β2-microglobulin（β2-MG）,urinary albumin excretion rate（UAER）,fasting plasma glucose,glycosylated hemoglobin,prothrombin time,platelet,activate partial thromboplastin time,fibrinogen and serum creatinine levels were tested.Estimated glomerular filtration rate was calculated.Results There was no statistically significant difference in gender,age,duration and body mass index among the patients with different rs16835198 genotypes（P>0.05）.The levels of TC,TG,LDL-C,Hcy,β2-MG and UAER in the blood of patients after treatment were significantly lower than before treatment.And the difference was statistically significant（P<0.05）.The levels of TC,TG,LDL-C,Hcy,β2-MG,and UAER in blood of patients with different rs16835198 genotypes were significantly different after treatment,among which the blood indicators in the patients with the genotype TT were the lowest,and those in the patients with the genotype GG was the highest,with statistically significant difference（P<0.05）.Conclusions Alprostadil has the best efficacy in the DN patient whose Irisin gene rs16835198 is TT type.